REDEFINE THE CONCEPT OF LONE WOLF IN THE CONTEXT OF GLOBAL JIHAD - Ashghor, Aly (Journal of Terrorism Studies, 2022)
The purpose of this article is to conceptualize or redefine the concept of "lone wolf” in the context of global jihad. This article uses a meta-analysis approach by proposing two literature review methods, namely an effort to track a number of literatures that are the basis for defining lone wolf acts of terrorism and tracking a number of literatures that discuss the phenomenon of global jihad. This article finds that there are no acts of global jihad terrorism that operate independently, technological developments have pushed the global jihad agenda by Islamic activism on a local scale through social media as an instrument of mobilization and communication without having to interact directly. Therefore, this article concludes that the concept of global jihad glocalization is more appropriately used to refer to acts of terrorism carried out independently by Islamic-based terrorism groups rather than using the term "lone wolf". For this reason, the glocalization of global jihad in the process of ideological doctrine or the process of becoming radicalized is no longer conventional but runs in virtual spaces of social media.